GITR ligand fusion protein agonist enhances the tumor antigen–specific CD8 T-cell response and leads to long-lasting memory - Durham, Nick M. (J Immunother Cancer, 2017)
BACKGROUND: The expansion of antigen-specific CD8 T cells is important in generating an effective and long-lasting immune response to tumors and viruses. Glucocorticoid-induced tumor necrosis factor receptor family-related receptor (GITR) is a co-stimulatory receptor that binds the GITR ligand (GITRL). Agonism of GITR can produce important signals that drive expansion of effector T cell populations. METHODS: We explored two separate murine tumor models, CT26 and TC-1, for responsiveness to GITR Ligand Fusion Protein(GITRL-FP) monotherapy. In TC-1, GITRL-FP was also combined with concurrent administration of an E7-SLP vaccine. We evaluated tumor growth inhibition by tumor volume measurements as well as changes in CD8 T cell populations and function including cytokine production using flow cytometry. Additionally, we interrogated how these therapies resulted in tumor antigen-specific responses using MHC-I dextramer staining and antigen-specific restimulations. RESULTS: In this study, we demonstrate that a GITR ligand fusion protein (GITRL-FP) is an effective modulator of antigen-specific CD8 T cells. In a CT26 mouse tumor model, GITRL-FP promoted expansion of antigen-specific T cells, depletion of regulatory T cells (Tregs), and generation of long-lasting CD8 T cell memory. This memory expansion was dependent on the dose of GITRL-FP and resulted in complete tumor clearance and protection from tumor rechallenge. In contrast, in TC-1 tumor–bearing mice, GITRL-FP monotherapy could not prime an antigen-specific CD8 T cell response and was unable to deplete Tregs. However, when combined with a vaccine targeting E7, treatment with GITRL-FP resulted in an augmentation of the vaccine-induced antigen-specific CD8 T cells, the depletion of Tregs, and a potent antitumor immune response. In both model systems, GITR levels on antigen-specific CD8 T cells were higher than on all other CD8 T cells, and GITRL-FP interacted directly with primed antigen-specific CD8 T cells. CONCLUSIONS: When taken together, our results demonstrate that the delivery of GITRL-FP as a therapeutic can promote anti-tumor responses in the presence of tumor-specific CD8 T cells. These findings support further study into combination partners for GITRL-FP that may augment CD8 T-cell priming as well as provide hypotheses that can be tested in human clinical trials exploring GITR agonists including GITRL-FP. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40425-017-0247-0) contains supplementary material, which is available to authorized users.